APLIKASI PENCATATAN KERUSAKAN DAN PERBAIKAN MESIN PENDINGIN BERBASIS ANDROID - rama_yani, liana; Ekawati, Nia (Computer Science and Industrial Engineering, 2021)
Showcase Cooler is a cooling machine that is used to preserve drinks and food so that they can be stored longer. In making repairs to the cooling machine currently still using paper which results in errors in recording data, wasteful use of paper because they have to recap data to be distributed to other parts. Android is a complex technology because it uses open source as the basis for the project that makes the smartphone operating system widely used today. The support for the software used in developing this application, namely Andoid Studio is a development software for developing android applications, Java functions as a programming language used to create software, and SQLite is a database that uses the user's internal storage device. This study uses the Black Box Testing method or functional testing because testing the software used without having to know the internal structure of the code or program. The resulting application is an android-based damage and repair recording system that is used for maintenance. Utilization of this technology so that maintenance can record repair damage to the machine using an Android-based smartphone in order to save on textbooks or paper media.